Explorative study on muscle strength and muscle strength ratios in top national and international badminton players - Felder, H.; Fröhlich, M.; Wey, J. (World Badminton Federation, 2016)
Badminton is a type of sport that is characterized by unilateral and bilateral physical load. The extent to which muscular imbalances are reflected in competitive badminton has been analyzed only in the context of shoulder rotation. Despite the fact that the entire body is used, badminton-specific studies have not been published concerning the lower extremity, trunk, cervical spine, and arms. Therefore, this study's objective is to obtain an overview of the muscular strength ratios and the strength values of the key badminton-specific muscle groups.